Derecho transnacional o la necesidad de superar el monismo y el dualismo en la teoría jurídica - Turégano Mansilla, Isabel (2017)
Law in a transnational context loses the features with which it has been configured since modernity. Classic distinctions between national and international, public and private, substantive and procedural, legal and political, social and legal lose their rigidity in a context of norms, orders, institutions and agents that interact and overlap in diverse and changing ways. A legal theory capable of explaining and evaluating this overflowing legal reality is lacking. A theoretical reflection on international law is not enough. Transnationalism appeals to a plurality of legal actors and spaces that interact to create, interpret and enforce rules which they mutually identify with. Transnationalism does not only refer to the global or the supranational, but to the interdependence of both with the local and transit spaces. And this translates into a change of focus or perspective that is required of each legal agent: management of the interrelation between diverse orders aimed to create spaces for approach, contestation and innovation is a normative requirement and it must be weighed against other legal values. Concepts to which legal theory must focus its attention change their meaning. The work refers to four of those concepts that I consider essential: social group or community, relations between orders and interlegality, coercion and normative diversity. The last part of the paper addresses the way in which these necessary changes have a place in our theories elaborated from the perspective of the great traditions of legal philosophy. What legal positivism, socio-legal theory and legal realism have in common might be an appropriate approach to the review of our discipline.